Large-Area SiPM Pixels (LASiPs): A cost-effective solution towards compact large SPECT cameras. (February 2021) - Guberman, D.; Paoletti, R.; Rugliancich, A.; Wunderlich, C.; Passeri, A.
Highlights: The feasibility of using Large-Area SiPM pixels (LASiPs) in SPECT is studied. LASiPs allow to reduce the weight and size of a full-body SPECT camera. SPECT cameras based on LASiPs can achieve similar performance to those based on PMTs. Geant4 simulations allow to extend the results to a large camera. Abstract: Single Photon Emission Computed Tomography (SPECT) scanners based on photomultiplier tubes (PMTs) are still largely employed in the clinical environment. A standard camera for full-body SPECT employs 50 -100 PMTs of 4–8 cm diameter and is shielded by a thick layer of lead, becoming a heavy and bulky system that can weight a few hundred kilograms. The volume, weight and cost of a camera can be significantly reduced if the PMTs are replaced by silicon photomultipliers (SiPMs). The main obstacle to use SiPMs in full-body SPECT is the limited size of their sensitive area. A few thousand channels would be needed to fill a camera if using the largest commercially-available SiPMs of 6 × 6 mm 2 . As a solution, we propose to use Large-Area SiPM Pixels (LASiPs), built by summing individual currents of several SiPMs into a single output. We developed a LASiP prototype that has a sensitive area 8 times larger than a 6 × 6 mm 2 SiPM. We built a proof-of-concept micro-camera consisting of a 40 × 40 × 8 mm 3 NaI(Tl) crystal coupled to 4 LASiPs. We evaluated its performance in a central region of 15 × 15 mm 2, where we were able to reconstruct images of a 99 m Tc capillary with an intrinsic spatial resolution of 2 mm and an energy resolution of 11.6 % at 140 keV. We used these measurements to validate Geant4 simulations of the system. This can be extended to simulate a larger camera with more and larger pixels, which could be used to optimize the implementation of LASiPs in large SPECT cameras. We provide some guidelines towards this implementation.